Argument ellipsis and the licensing of covert nominals in Bangla, Hindi and Malayalam - Andrew Simpson; Arunima Choudhury; Mythili Menon (Lingua, 2013)
This paper investigates the licensing of Argument Ellipsis/AE in three major languages of South Asia: Bangla, Malayalam and Hindi and a recent claim made in S ̧ ener and Takahashi (2009) and Takahashi (2011, in press) that the critical factor responsible for AE in null argument languages is the absence of verbal agreement. Observing and manipulating patterns of subject and object agreement in these languages, it is concluded that agreement does not appear to play a role in restricting AE. The paper then considers two other alternatives to the anti-agreement approach to AE (Hoji, 1998; Otaki, 2012), which instead relate the occurrence of AE to various interpretative and morphological properties of nominal elements, and emphasizes the important facilitating role that the use of anaphors frequently plays in the licensing of AE.